It's mine! - Lionni, Leo. (New York : Scholastic, 1986)
Three selfish frogs quarrel over who owns their pond and island until a storm makes them value the benefits of sharing.
Keywords: Frogs -- Fiction; Selfishness -- Fiction; Sharing -- Fiction